Albania : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper aims to determine how much of the economic slowdown of Albania is owing to cyclical conditions and how much to a reduction in potential growth. The analysis shows that average growth in 2009-14 dropped by 3.2 percentage points relative to 1997-2008, of which 2.8 percentage points are due to lower potential growth. Albania has significant potential to improve its export competitiveness. However, Albania's competitiveness has shown narrow improvements over the past five years, with weak productivity growth and continued concentration in low-skilled labor-intensive sectors with limited value added. This paper also explores the factors underpinning Albania's relatively low level of general government revenues.